Balidan : Stories of Indian's Greatest Para Special Forces Operatives - Pandey, Swapnil (Gurugram HarperCollins Publishers, 2023)
Few possess greater courage, yet remain in oblivion, than the Indian Para Special Forces. To these brave officers, worthy owners of the Balidan badge, is entrusted the safety of the most perilous heights and the annihilation of the darkest underbellies of terrorism. The legacy of these warriors is shrouded in mystery and legend. So secretive are their missions that little is known about them beyond code names like Dagger, Ghost, Viper or Desert Scorpio.In this remarkable collection of tales of valour beyond measure, Swapnil Pandey lifts the curtain on some of the greatest Special Forces officers and introduces readers to Colonel Santosh Mahadik, Captain Tushar Mahajan, Brigadier Saurabh Singh Shekhawat, Subedar Major Mahendra Singh and others.
Keywords: Security and Foreign Affairs; Military Affairs